Comparing Prognosis of Hip Replacement Outcomes with and without Post-Operative Physiotherapy Sessions: A Five-Year Retrospective Review (2018-2022) - Ijaz, Rimsha; Riaz, Saba; Maqbool, Sania (International Health Review, 2023)
The hip joint is a ball and socket joint that supports body weight and is responsible for locomotion. Hip replacement surgery is mostly performed when hip pain significantly impedes daily life activities and when non-surgical treatments are ineffective in certain cases. The most common cause of hip replacement is damaged hip joint, which can cause arthritis. Therefore, physical therapy after the replacement surgery of major joints is generally considered helpful for a good prognosis. However, if the patients are given the usual care recommended by the surgeons, the patients recover in the same manner as they do with the physical therapy sessions or the physical therapy usually accelerates the recovery process and prevents future complications. Thus, the current study provides a comprehensive of the recovery of patients who have undergone hip arthroplasty, with or without physical therapy training programs.